Apicoectomy of Perforated Root Canal Using Bioceramic Cement and Photodynamic Therapy - Abu Hasna, Amjad [UNESP]; Pereira Santos, Daiane; Gavlik De Oliveira, Tania Regina; Pinto, Alana Barbosa Alves [UNESP]; Pucci, César Rogerio [UNESP]; Lage-Marques, José Luiz (Hindawi, 2020)
Root perforation is a common endodontic accident. Its management depends mainly on root canal disinfection and sealing the perforation area by preventing any communication with the periodontium to prevent recontamination. A patient was referred to treat root perforation due to a previous treatment of tooth #22. The diagnosis was symptomatic periapical periodontitis, and the treatment plan was to retreat the root canal of #22 and make a surgical intervention (apicoectomy) associated with antimicrobial photodynamic therapy as a complementary technique. Five mineral oxides (5MO) cement was used as a root-end filling material. The procedures were performed in two sessions and controlled in two visits (after 30 days and 12 months). A bone neoformation was observed at the periapical area of tooth #22. 5MO bioceramic cement was effective in inducing the repair of the periapical lesion and had the ability to seal the exposed periapical area of the tooth. Its success depended mainly on root canal and surgical site disinfection.